Editorial - Katherine Bullock (American Journal of Islam and Society, 2009)
Even though interdisciplinary approaches to the study of humanity are increasingly a preferred method of study, it is still easy for scholars to isolate themselves within their field and lose touch with developments in the rest of the academy. Therefore, interdisciplinary journals such as AJISS are vital tools for helping them to keep abreast of the latest developments in areas outside their discipline but still in their realm of interest – in the case ofAJISS, the study of Islam andMuslims, both historically and contemporaneously. This issue of AJISS features outstanding essays from several academic disciplines: history, Islamic studies, management, and philosophy.We open withMuhammadAziz’s study of the rise of Sufism inYemen, “AShort Survey of Yemeni Sufism from Its Inception to the Thirteenth Century.” Aziz argues that a tradition of asceticism by Yemeni Muslims, including such prominent Companions as Abu Hurayrah, developed into themore institutionalized Sufismthat appeared and was spread by the Ayyubid dynasty during the eleventh to twelfth centuries. He maintains that tracing the history of Yemeni asceticism and Sufism is important because of the political, as well as religious, role that its leading practitioners had on Yemeni life ...